Combining Experts: Decomposition and Aggregation Order. Issue 6 (12th December 2012) - Baker, Erin; Olaleye, Olaitan
<x xml:space="preserve">Abstract</x> In this article we ask, if quantities in an elicitation have been decomposed, is it better to combine experts before or after recomposing the quantities? We find that combining experts earlier, before recomposition of the quantities, leads to smaller errors with less variance. A simulation shows that these differences may be quite small on average; while an application to actual data shows that the differences can be significant in individual decision problems.